KAJIAN KAPASITAS KELEMBAGAAN KELOMPOK TANI HUTAN KEMASYARAKATAN DI KECAMATAN PELAIHARI KABUPATEN TANAH LAUT - Muhammad Rifa’i; Hafizianor Hafizianor; Hamdani Fauzi (Jurnal Sylva Scienteae, 2020)
The study concern to review the institutional capacity of the Community Forestry Farming Group (HKm) in Pelaihari District, Tanah Laut Regency. This study uses a qualitative approach and the object of this research is Harapan Bersama Farmers Group Ujung Batu Village, Karya Jaya Farmers Group, Ambungan Village and Kelurahan Karang Taruna  Karya Usaha Group in Pelaihari District, Tanah Laut Regency. Data was analized bay using the Levis modification formula.This study shows the innovativeness variable 63%, 62.6% sustainability, effectiveness of functions and roles 63%.Based on those three components value, the HKm institutional capacity is categorized as high because HKm can run well supported by institutional capacity, the role of extension agents, outside party support, member characteristics, member capacity, the role of farmer group leaders, dynamic HKm farmer groups and High participation of members on this HKm program.Keywords: Capacity, Institutional, Variable